Clear Cell Papillary Renal Cell Carcinoma – A New Emerging Entity - Sinnott, MD, Michael; Chen, MD, PhD, Frank; Kanehira, MD, Kazunori; Sule, MD, PhD, Nobert; Xu, MD, PhD, Bo (North American Journal of Medicine and Science, 2012)
Clear cell papillary renal cell carcinoma was initially reported in patients with end stage renal disease under name of “end stage renal disease-associated renal cell carcinoma”. However, subsequent studies show that the tumor is also seen in non-end stage settings with or without impaired renal function. Recent advances in molecular genetic techniques and immunohistochemical staining have showed that clear cell papillary renal cell carcinoma is a new distinct entity that has unique genetic, histomorphological and clinical characteristics. This review summarizes the most current views on clear cell papillary renal cell carcinoma with focus on histomorphological features, immunohistochemical profiles and molecular genetic characteristic of this new entity.